2020
DOI: 10.3233/jpd-202069
|View full text |Cite
|
Sign up to set email alerts
|

Management of Pain in Parkinson’s Disease

Abstract: Pain is a very frequent symptom with influence on the quality of life in Parkinson’s disease (PD), but is still underdiagnosed and commonly treated only unsystematically. Pain etiology and pain character are often complex and multi-causal, and data regarding treatment recommendations are limited. Pain can be primarily related to PD but frequently it is associated with secondary diseases, such as arthrosis of the spine or joints. However, even basically PD-unrelated pain often is amplified by motor- or non-moto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 107 publications
(186 reference statements)
2
42
0
3
Order By: Relevance
“…In another randomized placebo-controlled trial, injection of incobotulinumtoxinA with 100 units into either the flexor digitorum brevis or flexor digitorum longus was effective in reducing pain associated with plantar flexion of toe dystonia [ 49 ]. Finally, as discussed previously, BoNT can help with painful myotonus or spasms in the esophagus, pylorus, anal sphincter, and detrustor muscle [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another randomized placebo-controlled trial, injection of incobotulinumtoxinA with 100 units into either the flexor digitorum brevis or flexor digitorum longus was effective in reducing pain associated with plantar flexion of toe dystonia [ 49 ]. Finally, as discussed previously, BoNT can help with painful myotonus or spasms in the esophagus, pylorus, anal sphincter, and detrustor muscle [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that physicians need to pay more attention to the occurrence of non-motor symptoms, especially pain, which was the sensory impairment most commonly reported by patients, exceeding mentions of constipation, mood disorder or unexpected olfactory impairment. A previous study showed that pain was ranked highly as a troublesome symptom in all stages of the disease and was particularly frequent in early-stage PD (18,19). Separating PD-related pain from pain of other origins is an important challenge due to a phenomenon known as "many syndromes under the same umbrella" (18); ∼40% of patients may not report this complaint in routine visits to a physician (20).…”
Section: Discussionmentioning
confidence: 99%
“…Monoamine oxidase inhibitors (MAOI-B), such as selegiline, may also be beneficial in treating PD related pain. A post-hoc analysis revealed that safinamide reduced the number of concomitant pain treatments that PD patients relied on, and also the scores of the “bodily discomfort” domain of the Parkinson’s Disease Questionnaire-39 [ 84 , 94 , 95 ].…”
Section: Treatment Of Chronic Pain In Parkinson’s Diseasementioning
confidence: 99%
“…As with the dopaminergic agents, there is a paucity of literature examining other pharmacologic agents in the treatment of chronic pain in PD. Nonsteroidal anti-inflammatory drugs (NSAIDs) such as ibuprofen and diclofenac were reported by PD patients to be the medication most frequently used to treat their pain [ 94 ]. The use of these drugs has not been linked to constipation.…”
Section: Treatment Of Chronic Pain In Parkinson’s Diseasementioning
confidence: 99%
See 1 more Smart Citation